The impact of character presence and entertainment value on brand recall and brand attitude in advergame - Azaze @ Azizi Abdul Adis; Hyung Jun Kim; Grace Phang Ing; Mohd Rizwan Abdul Majid; Zaiton Osman; Izyanti Awang Razli (INSInet Publications, 2015)
The increase of online advertising, in particular advergame, has become popular method in strengthening consumer brand recognition by inserting attractive characters and entertainment value. Studies on using spokes-characters in advertising effectiveness had showed convincing result in marketing communication. However, few studies have examined the link between character presence and consumers‟ brand recall and attitude in advergame. Moreover, how the entertainment value of an advergame influences brand recall and brand attitude and the mediating role of brand recall in influencing character presence and entertainment on brand attitude are still lacking in the advergaming literature. Objective: This paper examines the influence of character presence and entertainment on brand recall and brand attitude in advergame. Results: Using structural equation modeling, the results showed that character presence had no influence but entertainment value had a positive influence on brand recall and brand attitude. This study confirmed the role of brand recall as a mediator of the effect of between entertainment and brand attitude in advergame. Conclusion: This study fills the gap of the relationship between character presence and entertainment on brand recall and attitude in advergame.